Nodule ultrastructure and initial growth of Anadenanthera peregrina (L.) Speg. var. falcata (Benth.) Altschul plants infected with rhizobia - Gross, E.; Cordeiro, L.; Caetano, F. H. (Oxford University Press, 2002)
The anatomy and ultrastructure of root nodules of Anadenanthera peregrina var. falcata (Leguminosae-Mimosoideae) were analysed, as was plant growth. To ensure that nodules developed, seedlings were inoculated with a mixture of six strains of rhizobia. Nodules were produced that differed in appearance-and probably also effectiveness-but their structure was similar and they showed characteristics typical of indeterminate nodules, such as persistent meristematic tissue and a gradient of cells at different stages of development. Many starch grains were present in inner cortex cells and interstitial cells of infected tissue. Infected cells were densely packed with bacteroids, which contained many poly-beta-hydroxybutyrate granules. The high incidence of these granules, together with high levels of starch accumulation in interstitial cells, suggested low N-2-fixation efficiency of the rhizobia isolates used for inoculation. In the symbiosomes of early-senescent infected cells, reticulum-like structures, small vesicles and a fibrillar material were observed; these may be related to bacteroid degradation. In the cytoplasm of late-senescent infected cells, many vesicles and membrane-like structures were observed, probably associated with membrane degradation of bacteroids and peribacteroids. The total biomass of plants inoculated with rhizobia was low and their xylopodia and shoots had low levels of N compared with non-inoculated plants fertilized with ammonium nitrate. However, inoculated plants did not show N-deficiency symptoms and grew better than non-inoculated plants without N fertilization. These growth results, together with ultrastructural observations of nodules, suggest that nitrogen fixation of rhizobia isolates associated with Anadenanthera peregrina var. falcata roots is poor. (C) 2002 Annals of Botany Company.
Keywords: nodule anatomy; nodule ultrastructure; Anadenanthera peregrina Var. falcata; angico do cerrado; rhizobia; plant growth; N content; nodule development; nodule senescence; xylopodium; nitrogen fixation; Brazilian savanna